Mass Transport to Nanoelectrode Arrays and Limitations of the Diffusion Domain Approach: Theory and Experiment - Godino, N; Borrise, X; Xavier Munoz, F; Javier del Campo, F; Compton, R (2009)
The diffusion domain approach is a general framework for the understanding, interpretation, and prediction of the response of microelectrode arrays. This work exposes some of its limitations, particularly when dealing with nanoelectrode arrays of a few micrometers in size. This article also provides an overview of the principles and assumptions underpinning the diffusion domain approach, and then applies it to the study to approach, which is then applied to the study of nanoelectrode arrays. The apparent disagreement between theory and experimental data, due to the importance of radial diffusion to nanoelectrode arrays compared to microelectrode arrays, is explained by using simulations and experiments. The principle that an array of micro- or nanoelectrodes eventually behaves as if the entire array were a single electrode of the size of the array, with its corresponding properties, always applies. However, while microelectrode arrays tend to behave as macroelectrodes, nanoelectrode arrays on the other hand may behave as microelectrodes. For the case of arrays of small numbers of electrodes, or array sizes of micrometers or less, this compromises one of the key assumptions of the diffusion domain approach, namely that inner electrodes in an array are equivalent, which may lead the unaware to erroneous conclusions. © 2009 American Chemical Society.